2006
DOI: 10.1007/s11060-006-9292-0
|View full text |Cite
|
Sign up to set email alerts
|

Frequent hypermethylation of the DNA repair gene MGMT in long-term survivors of glioblastoma multiforme

Abstract: We have performed a methylation-specific PCR approach to comparatively analyze the MGMT promoter methylation status in 186 glioblastomas (GBM) from patients with classic survival and nine from patients with long-term survival (LTS GBM). The methylation rate in LTS GBM was significantly higher (77.8% vs. 39.2%, P = 0.033) which suggests that MGMT hypermethylation is a frequent hallmark of LTS GBM and contributes to characterize this intriguing GBM subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
51
1
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 3 publications
9
51
1
4
Order By: Relevance
“…The dependency of MGMT on the expression levels of mGlu3 receptors might help to explain the controversial data on the correlation between MGMT promoter methylation and patients' survival. [34][35][36][37][38][39][40] Our data may pave the way to a new strategy in the pharmacological treatment of malignant gliomas because mGlu3 receptor antagonists could be added to temozolomide or other DNA-alkylating agents for the optimization of adjuvant chemotherapy. The evidence that a combined treatment with temozolomide and LY341495 was still efficacious in restraining tumor growth when initiated 45 days after cell implantation in mice is particularly promising for translation into medical practice because of the long interval between onset and treatment of malignant gliomas.…”
Section: Discussionmentioning
confidence: 87%
“…The dependency of MGMT on the expression levels of mGlu3 receptors might help to explain the controversial data on the correlation between MGMT promoter methylation and patients' survival. [34][35][36][37][38][39][40] Our data may pave the way to a new strategy in the pharmacological treatment of malignant gliomas because mGlu3 receptor antagonists could be added to temozolomide or other DNA-alkylating agents for the optimization of adjuvant chemotherapy. The evidence that a combined treatment with temozolomide and LY341495 was still efficacious in restraining tumor growth when initiated 45 days after cell implantation in mice is particularly promising for translation into medical practice because of the long interval between onset and treatment of malignant gliomas.…”
Section: Discussionmentioning
confidence: 87%
“…PTEN. [7][8][9] Recent studies demonstrated that mutations in IDH1 10 and alterations in multiple networking genes (POLD2, CYCS, MYC, AKR1C3, YME1L1, ANXA7, and PDCD4) 11 were associated with GBM survival. Polymorphisms in TERT, 12 IL4R, 13 EGF, 14,15 and CX3CR1 16 genes and GBM survival have also been described.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, with decreased expression of MGMT, because of methylation of its promoter, the therapeutic efficacy of temozolomide is enhanced. 89 That patient survival times differ according to MGMT status underscores the significance of understanding the diversity of tumor biology. Such an understanding can be of immense importance with regard to CSCs because activity of MGMT has been shown to be 32-to 56-fold higher in CD133-positive than in CD133-negative cells, leading to increased resistance to temozolomide.…”
mentioning
confidence: 99%